Parental Burnout Assessment (PBA) in Different Hispanic Countries: An Exploratory Structural Equation Modeling Approach - Manrique-Millones, Denisse; Vasin, Georgy M.; Dominguez-Lara, Sergio; Millones-Rivalles, Rosa; Ricci, Ricardo T.; Abregu Rey, Milagros; Escobar, María Josefina; Oyarce, Daniela; Pérez-Díaz, Pablo; Santelices, María Pía; Pineda-Marín, Claudia; Tapia, Javier; et al. (Frontiers in Psychology, 2022)
Parental burnout is a unique and context-specific syndrome resulting from a chronic imbalance of risks over resources in the parenting domain. The current research aims to evaluate the psychometric properties of the Spanish version of the Parental Burnout Assessment (PBA) across Spanish-speaking countries with two consecutive studies. In Study 1, we analyzed the data through a bifactor model within an Exploratory Structural Equation Modeling (ESEM) on the pooled sample of participants (N = 1,979) obtaining good fit indices. We then attained measurement invariance across both gender and countries in a set of nested models with gradually increasing parameter constraints. Latent means comparisons across countries showed that among the participants countries, Chile had the highest parental burnout score, likewise, comparisons across gender evidenced that mothers displayed higher scores than fathers, as shown in previous studies. Reliability coefficients were high. In Study 2 (N = 1,171), we tested the relations between parental burnout and three specific consequences, i.e., escape and suicidal ideations, parental neglect and parental violence towards one's children. The medium to large associations found provided support for the PBA's predictive validity. Overall, we concluded that the Spanish version of the PBA has good psychometric properties. The results support its relevance for the assessment of parental burnout among Spanish-speaking parents, offering new opportunities for cross-cultural research in the parenting domain.